Nurse’s Perception of Family Presence during Dressing Change in the Adult: a Study in Burn Intensive Care Unit (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Burn injuries can be devastating to both the patients affected and the patients’ families who support the injured person. In an effort to shield patients’ family members from and anxiety-provoking experience and protect the patients from potential infections, burn units have historically restricted visitation during dressing change but evidence indicates that these restrictions contribute to patients’ and family’s dissatisfaction and to their knowledge deficit when it comes time to care for burn patients at home. Thus this study assess the nurse’s perception of family presence during dressing change in the adult burn intensive care unit of selected tertiary care hospital in India.Material and Methods: A Non- Experimental Descriptive Survey Design with evaluative research approach was used to evaluate the nurse’s perception of Family Presence during dressing change in the Adult Burn Intensive Care Unit of KLES Dr. Prabhakar Kore Hospital and Medical Research Centre, Belagavi, India. A total of 30 nurses working in Adult Burn Intensive Care Unit (BICU) were selected by using the non-probability convenience method of sampling technique. A 5 points Likert scale was used for data collection.Results: The study findings showed that, Majority 22 (73.3%) of the nurses had performed dressing more than 11 times but 26 (86.7%) of the nurses had never experienced family member in dressing room during dressing and 28 (93.37%) of the nurses had never initiate family member during dressing change as well as majority 21 (70%) of the nurses had never experience of family request to be on dressing room during dressing change. Majority 12 (40%) of the nurses were disagree on family presence during dressing change, 10 (33.3%) of the nurses were had neutral perception where as minority nurses 8 (26.7) had agree regarding family presence during dressing change.Conclusion: The study revealed that majority of the nurses does not agree to have family member to be in room during dressing change even though presence of family members during dressing change will have a positive effect on patient, family, nurse, satisfaction with hospital care.